Science Teaching Materials Based Jayapura Ethnoscience and Their Impact on Students' Science Process Skills - Jan Pieter; Putu Victoria M. Risamasu (Postgraduate, University of Mataram, 2025)
Students living in a dominant culture need science teaching materials that are able to mediate the transition of life from traditional science to scientific science. The solution offered is the application of ethnoscience in science learning. The purpose of the study was to develop ethnoscience-based science teaching materials and see its impact on students' science process skills. The type of research is research and development (Borg & Gall, 2003). The population of the study was grade VII students from four junior high schools in Jayapura City. The research sample consisted of eight classes, namely four classes as experimental classes that learned with Jayapura ethnoscience-based teaching materials and four classes as control classes with conventional teaching materials. Furthermore, a quasi-experiment was used using a randomized pretest-posttest control group design. The results of the study showed that with the reconstruction carried out, many traditional sciences were found that could be used to teach modern science. The developed Jayapura ethnoscience-based science teaching materials had a positive impact, and there was a significant difference in science process skills between students in the experimental and control classes. The developed Jayapura ethnoscience teaching materials were able to mediate students' learning transitions and support students' science process skills in learning science.